High-raised buildings in urban area contributes to the snatch theft incidents / Anith Nabilah Mustafa and Siti Rasidah Md Sakip - Anith Nabilah, Mustafa; Siti Rasidah, Md Sakip (Universiti Teknologi MARA, Perak, 2017)
Snatch theft incidents are on the rise in Malaysia especially in the cities. It tendsto happen in cities because there is a possibility to commit it and both crime and urban are often associated with each other. The aim of this paper is to find out whether the buildings with two or more levels in urban area contributes to the snatch theft incidents. The present study has been taken up to detect the hotspots of snatch theft in Selangor, Malaysia. The crime data were obtained by requesting and analysing the index crime statistical data from the Royal Malaysian Police (RMP). This study made use of the Geographical Information System (GIS) where its 3D modelling function to construct, assess and analyse the area with high snatch theft cases. The crime reports of 2010 until 2015 were geocoded and the crime maps were prepared in ArcGIS 10.2. It was found that the hotspot area is a mix-used development area which consists mainly of commercial and residential areas of more than two-level buildings.